Effect of Organic manure and Jeevamrit on growth yield and quality of radish (Raphanus sativus L.) under U.P. condiotion - Srivastava, Deepti; Singh, S P; Yadava, LP; Singh, J K; Singh, Richa (International Journal of Environment, Agriculture and Biotechnology, 2024)
Radish is one of the well-known root crop and its popularity could be due to its wider climatic adaptation, easy cultivation method and a wider range of its uses. Excessive chemical fertilizer could lead to chemical toxicity in the root crop and affected the growth and yield of radish. A field experiment was assessed to conducted in randomized block design with five treatment and three replications with the setup of T1 –Without manuring,T2-FYM @5Tha-1 +Vermicompost@ 1.75Tha-1+ jeevamrit@5%conc, T3-FYM@5Tha-1+vermicompost@1.75Tha-1 +jeevamrit@ 10%conc, T4-FYM @2.5Tha-1 +Vermicompost @.087Tha-1+jeevmrit@5% conc and T5-FYM @2.5 Tha-1+Vermicompost@ 0.87Tha-1 +jeevamrit @10% conc. respectively to evaluate the effect of organic manure and jeevamrit on growth, yield and quality of radish.The results revealed that treatment T3 -FYM@5Tha-1+vermicompost@1.75Tha-1 +jeevamrit@ 10%conc were significantly enhanced the growth characters i.e. number of leaves(28.67)at 120 DAS, leaf length(26.63cm) at 120DAS , Leaf breadth(6.06cm) after 120 DAS whereas, yield characters i.e. root length (26.16cm),root diameter(3.79cm),TSS(5.250B),Fresh weight of root(20.16g),fresh weight of plant(61.21g), yield(224.64gha-1), were also found highest with T3-FYM@ 5Tha-1+vermicompost@1.75Tha-1 +jeevamrit 10% conc. The study suggested that the application of jeevamrit along with organic manures was found more beneficial and significantly improved the growth and yield of radish under U.P. condition.